Food security and dietary intake of a cohort of South African students during COVID-19 - Juanita Jonker; Corinna Walsh (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences)
Background: Food insecurity among students was a global concern even before the coronavirus disease 2019 (COVID-19) pandemic. Food security comprises having access to sufficient, safe and nutritious food at all times. The COVID-19 containment measures negatively influenced economies, impacting citizens’ food security.